Using a design-based research approach for a supplementary instruction programme: A pedagogical intervention during the COVID-19 pandemic - Mutanda, T.; Gumede, P. R.; Mayisela, T.; Ng’ambi, D. (South African Journal of Higher Education, 2023)
The study focused on the implementation of supplementary instruction as a suitable and effective pedagogical intervention for assisting at-risk students enrolled in an Advanced Research Methodology core course in one of the South African higher education institutions (HEIs). Supplementary instruction (SI) has been purported to be an effective technique for assisting at-risk students undertaking high-risk core modules. The educational challenge of at-risk students in higher education has been worsened by the emergence of the COVID-19 pandemic where high-risk core modules implementing e-learning posed serious challenges for at-risk students thereby negatively affecting pass rates and throughput. The design-based research (DBR) approach was used to guide the design of the intervention and research its effectiveness. The article reports on the design principles that yielded these results. After one cycle of DBR, it was established that SI had a positive impact on the pass rates of this particular course. The article argues that the use of the proposed designed principles in SI interventions has the potential to increase higher mean grades, lower failure and withdrawal rates, and higher retention rates of students. However, this study recommends that further iterations must be undertaken to refine design principles for an SI programme of this nature. The pedagogical significance of the current study in the prevailing circumstances and post COVID-19 pandemic is implementing a robust SI intervention in all core modules at the University of Technology.